2019
DOI: 10.5505/turkhijyen.2019.97268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some food safety-related characteristics of Enterococcus faecium and Enterococcus faecalis strains isolated from raw fish samples

Abstract: Çiğ balık örneklerinden izole edilen Enterococcus faecium ve Enterococcus faecalis suşlarının gıda güvenliği yönünden bazı özelliklerinin değerlendirilmesi Evaluation of some food safety-related characteristics of Enterococcus faecium and Enterococcus faecalis strains isolated from raw fish samples Onur KARAALİOĞLU 1 , Sine ÖZMEN-TOĞAY 1 , Mustafa AY 2 , Gözde SOYSAL 1 , Mine ÇARDAK 3 , Ufuk BAĞCI 4 , Özlem EROL-TINAZTEPE 5 ÖZET Amaç: Bu çalışmada çiğ balık örneklerinden izole edilen Enterococcus faecium ve E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A total of 116 isolates were determined to belong to the genus Enterococcus and these isolates were identified at the species level (Project Final report). According to the identification results of the isolates at the species level, it was observed that Enterococcus gallinarum and E. casseliflavus constitute the dominant flora in both raw and processed products followed by E. durs, E. faecium and E. hirae (Project Final report, Karaalioğlu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 116 isolates were determined to belong to the genus Enterococcus and these isolates were identified at the species level (Project Final report). According to the identification results of the isolates at the species level, it was observed that Enterococcus gallinarum and E. casseliflavus constitute the dominant flora in both raw and processed products followed by E. durs, E. faecium and E. hirae (Project Final report, Karaalioğlu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…After the incubation period, for each sample, 3-5 colonies were selected from the typical colonies grown on the CAA agar medium and purified again using the same medium. After purification of colonies, they were stored in 30% glycerol at -20°C for further analysis (Baixas-Nogueras et al, 2003, Karaalioğlu et al, 2019Çardak et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation